Human Development and Income Inequality in D-8 Countries: A Maqashid Sharia Perspective - Shofiatul Hilwa; Triandhari, Risna; Parianom, Raden (Faculty of Economic and Business, Universitas Islam Negeri Syarif Hidayatullah, 2026)
Research Originality: This study is original in applying a Maqashid Sharia-based human development index to examine the short- and long-run effects of human development on income inequality in D-8 countries. Research Objectives: This study aims to analyze whether human development based on the Maqashid Sharia framework can effectively reduce income inequality in D-8 countries in both the short run and the long run. Research Methods: Using panel data from eight D-8 countries during 2003–2022, income inequality is measured by the Gini index and the Palma ratio, while human development is represented by the Maqashid Sharia Index (MSI). The analysis employs a Panel ARDL model with the Pooled Mean Group estimator to capture short-run and long-run relationships. Empirical Results: The results show that Maqashid Sharia-based human development significantly reduces income inequality in the long run across D-8 countries, reflecting the maslahah-oriented approach of Islamic economic development. In the short run, it reduces inequality in Indonesia and Turkey but increases inequality in Bangladesh, Egypt, and Nigeria. Implications: These findings suggest that human development policies should incorporate moral and value-based dimensions. Policymakers in D-8 countries need to promote not only education, health, and income, but also ethical values to ensure more equitable income distribution. JEL Classification: C33, F22, I32, J61, J62